(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Draksha (Mrudwika) is best among all fruits as per Ayurveda. It is also indicated in different diseases as a medication and used in diets in fresh and dry forms. Draksha is a fruit that is only available during certain times of the year. Sharkara dosage form of it can be prepared to make that is palatable. Draksha is used in dry form i.e., Munakka (Mrudwika, raisins). Commonly, Munakka, Kismis, and Currants are three varieties with slight differences in their characteristics and nutritional content. They own property in Mridu Rechana, Vatahara, Pittahara, Brimhana, Vrishya, and Rasayana. For health promotion, disease prevention, and a wide range of Vata, Pitta, and Raktaja Vyadhis and Apatarpana Vyadhis, Draksha should be regularly incorporated into diet in either dry or fresh form. In the present study, an attempt has been made to develop pharmacognostical and pharmaceutical standards for Mrudwika Sharkara for assurance of quality of herbal compounds pharmacognostical and pharmaceutical analysis should be done. Methods: Mrudwika Sharkara was subjected to microscopic evaluation for pharmacognostical study, analysis physic-chemical analysis includes specific gravity, pH value, reducing sugar, non-reducing sugar and total sugar and high Performance thin layer chromatography (HPTLC). Mrudwika Sharkara was assessed for microbiological which include smear examination and culture study. Results: Pharmacognostical study showed the presence of certain identifying characters of Mrudwika and Sharkara. In pharmaceutical study, preliminary physico-chemical analysis showed specific gravity is 1.160, pH value is 4, reducing sugar 21.1%, non reducing sugar 48%, total sugar content 69.1%. HPTLC analysis showed eight spots in 254nm and six spots in 366nm. From date of preparation 23/06/21 to 18/10/22 no fungal contamination was found in Mrudwika Sharkar Conclusion: Present work was carried out to standardize the formulation Mrudwika Sharkara in terms of its identity, quality and purity. All of the preparation’s active ingredients were identified by pharmacognostic and physicochemical examination. Self life of Mrudwika Sharkara showed that the quality of syrup in standard condition.